A community based study of breast feeding and weaning practices among mothers in urban field practice area of SRTR, GMC, Ambajogai - Shaikh, Mohammed Rehan; Nagaonkar, A. S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Mother’s milk is the best gift nature has provided. Practicing exclusive breastfeeding for 6 months is the simplest, healthiest and least expensive feeding method that fulfills the infant’s needs for nutrition and growth. Breast feeding is a common practice in India but factors influences breast feeding practice such as gender inequity, lack of knowledge, social pressure, pre-lacteal feed, illness among the lactating mother etc. Study of socio demographic factors and pattern of breast feeding and weaning practices in urban field practice area. Methods: A cross-section study was conduct in Urban Health Center of Govt. medical college and hospital of Ambajogai, Maharashtra. Mothers who are having a child between 0-24 months of age of both sexes were included in this study and interviewed. Results: Out of 193 women’s, most of the mothers were aged less than 25 years (78.04%) and were Hindus (73.9%). Most were illiterate (68.30) and belonged to the class V (97.5%), majority were housewives (99.1%) and multiparous (68.2%). Most had initiated breastfeeding (78.8%) within 24 hours of delivery. About 15.4% of the infants did not receive colostrums and 22.8% of the infants were not exclusively breastfed. Ghutti (water mixed with honey and herbs), boiled water, tea, and animal milk were commonly used pre-lacteal feeds. Conclusions: Despite higher rates of early initiation of breastfeeding and exclusive breastfeeding, awareness of the benefits of exclusive breastfeeding was low. Indicates need to promote awareness of the correct method of infant feeding and care of the newborn.